Preventing Tuberculosis Transmission at Home: a Literature Review - Noviana, Ineke; Landudjama, Leni (Journal of Tropical Diseases and Health Science, 2024)
Pulmonary tuberculosis (TB) remains one of the major public health challenges in Indonesia and a key obstacle to achieving the 2030 TB elimination target. Transmission most frequently occurs within households, particularly among family members living with active TB patients. Poor home conditions—such as inadequate ventilation, limited natural lighting, and overcrowding—are major factors facilitating transmission. This study aims to identify effective household-level prevention strategies for pulmonary TB through a literature review of ten studies published between 2020 and 2024. A literature review design was employed using the PRISMA approach to select relevant articles from Google Scholar, with the keyword “TB transmission prevention at home.” Data were analyzed using the PICO framework to define population, intervention, comparison, and outcomes. The findings revealed five main prevention themes: improvement of household environments, education and behavioral change, contact investigation and preventive therapy (TPT), strengthening the role of health workers and community cadres, and context-specific strategies for Eastern Indonesia. The study concludes that preventing household TB transmission requires a multidimensional and community-based approach. Comprehensive preventive measures at the household level are crucial to support Indonesia’s goal of TB elimination